Correlation Anxiety, Self confidence and Motivation Toward Athlete’s Performance of Tunas Volleyball Club Pekalongan (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This study aims to determine (1) Analyze the contribution of anxiety to athlete performance, (2) Analyze the contribution of self self confidence to athlete's performance, (3) Analyze the contribution of motivation to athlete's performance, (4) Analyze the contribution of anxiety, self confidence, and motivation to athlete performance. This research uses correlation method. Population in this research is volleyball atlet of Tunas Pekalongan which amounts 42 person athletes. The sample in this research is 30 male athletes taken by purposive sampling technique (Gender, Age). Variables in this research consist of three variables: Anxiety (X1), Self Self confidence (X3), and Motivation (X3) while the dependent variable is Y Volley Ball Athlete). Instruments and techniques of data collection using tests. Data analysis technique using path analysis technique with prerequisite test that is test of normality, linearity and multicolinearity. The results showed that the performance to athlete received significant contribution from Anxiety of 45.02%, Self Self confidence of 32.15%. Motivation of 57.61%. Anxiety, Self Self confidence, and Motivation of 65.50%. The conclusion of this research is the factor of anxiety, self confidence, and motivation has contributed to the performance both alone and together.